Nilai-nilai Shidiq “Tokoh Rayya” pada Novel Sekosong Jiwa Kadaver Karya Ita Fajria Tamim - Fani, Khori Fuad; Saputra, Edi (Lembaga Yasin AlSys, 2024)
Shidiq is a part of akhlaq that has a major role to be in harmony with other akhlaq. If a person does not have akhlaq shidiq then a person will find it difficult in social life and difficult to be trusted by others. This study uses the content analysis method to obtain data on shidiq values in the novel As empty as a cadaveric soul. by Ita Fajria Tamim with Rayya as a sample. The instrument in this study is a human instrument or own research. The data collection techniques used are coding sheets and literature studies. The technique of analyzing data in this study is to fill in the coding sheet according to the measurement tools that have been set, conduct validity tests, and compile data in units of analysis so that it can be categorized and interpreted to conclude the study. It can be concluded from this research that in the novel Sekosong Jiwa Kadaver by Ita Fajria Tamim, it has been found indeed there is the true value of will, the true value of words, the true value of promises, and the true value of relationships. and no true value of reality is found in it.